2016
DOI: 10.1055/s-0035-1569272
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 1 Regulates the Expression of ATP-Binding Cassette Transporter A1 in Pancreatic Beta Cells

Abstract: ATP-binding cassette transporter A1 (ABCA1) in pancreatic beta cells influences insulin secretion and cholesterol homeostasis. The present study investigates whether insulin-like growth factor 1 (IGF-1), which mediates stimulation of ABCA1 gene expression, could also interfere with the phosphatidylinositol 3-kinase (PI3-K) cascade.ABCA1 expression was examined by real-time polymerase chain reaction (PCR), Western blot analysis, and a reporter gene assay in rat insulin-secreting INS-1 cells incubated with IGF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Foxo1 KD and inhibition reduced E2-dependent ERα transcriptional activity through the ERE, similar to the effect of Foxo1-ERα interaction on the ERE in MCF7 cells [26]. E2 enhanced Foxo1 phosphorylation in INS1-E and human islets, a known mechanism of Foxo1 nuclear export and inhibition of transcription [28,35]. E2 could thus act to limit its transcriptional collaboration with Foxo1 by time dependent induction of phosphorylation (proposed model ▶Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Foxo1 KD and inhibition reduced E2-dependent ERα transcriptional activity through the ERE, similar to the effect of Foxo1-ERα interaction on the ERE in MCF7 cells [26]. E2 enhanced Foxo1 phosphorylation in INS1-E and human islets, a known mechanism of Foxo1 nuclear export and inhibition of transcription [28,35]. E2 could thus act to limit its transcriptional collaboration with Foxo1 by time dependent induction of phosphorylation (proposed model ▶Fig.…”
Section: Discussionmentioning
confidence: 74%
“…In accord with the latter effects, Foxo1 haploinsufficiency enhances proliferation and restores β-cell mass in insulin receptor substrate-2-knockout and β-cell-specific Pdk1-knockout models of diabetes [23,24]. Foxo1 activity is regulated by post-translational modifications, primarily phosphorylation, which induces nuclear-cytoplasmic translocation thus inhibiting its transcriptional activity [25][26][27][28].…”
mentioning
confidence: 91%
“…However, there is a debate regarding whether the ABCA1 gene polymorphism is a genetic risk factor for T2DM [ 35 , 85 ]. Insulin-like growth factor 1 (IGF-1) can mediate the stimulation of ABCA1 gene expression by inducing the PI3-K/Akt/Forkhead box protein O1 (FoxO1) pathway [ 86 ]. In addition, the expression of ABCA1 and miR-27a can be increased and decreased, respectively, via GLP-1.…”
Section: Abc Transporters and Metabolic Diseases: Abnormal Lipid Metamentioning
confidence: 99%
“…The important role of β-cell ABCA1 in glucose homeostasis was further underscored by the finding that rosiglitazone increased β-cell ABCA1 expression (Brunham et al 2007). Furthermore, we previously found that exendin-4, a glucagon-like peptide-1 analog, and insulin-like growth factor-I, have stimulatory effects on ABCA-1 expression at the transcriptional level, thereby influencing insulin secretion in pancreatic β-cells (Li et al 2010, Lyu et al 2016.…”
Section: Discussionmentioning
confidence: 97%
“…To measure cellular cholesterol content concentration, we used a colorimetric assay that utilizes reagents widely used for the measurement of cholesterol in conjunction with a random-access chemistry analyzer ARCHITECT c8000 as described previously (Lyu et al 2016).…”
Section: Cholesterol Content Assaymentioning
confidence: 99%